The Effect of Positive Emotions on Employee Performance: The Mediating Role of Turnover Intention - Yani Abdurrahman, Ahmad; A Kamis, Ruslan (Jurnal MS, 2025)
Objective: This study investigates the effect of positive emotions on employee performance, with turnover intention as a mediating variable, in the context of Islamic banking. It seeks to determine whether positive emotions directly enhance performance and indirectly do so by reducing turnover intention. Methodology: A quantitative survey was conducted among employees of four Islamic banks in North Maluku: Bank Muamalat, Bank Syariah Indonesia (BSI), Bank Pembiayaan Rakyat Syariah (BPRS), and Bobato Lestari Syariah comprising 185 employees. Using Slovin’s formula with a 5% margin of error, 127 respondents were selected through simple random sampling (SRS). The sample size exceeded the minimum requirement for PLS-SEM based on Cohen’s guideline and G*Power analysis. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1.4, evaluating both direct and mediating effects. Findings: Results indicate that positive emotions significantly reduce turnover intention and enhance employee performance. Turnover intention negatively affects performance and partially mediates the relationship between positive emotions and performance. Conclusion: Strengthening positive emotions is essential for improving employee performance and reducing turnover intention in Islamic banks. Theoretically, this study extends the Broaden-and-Build Theory by incorporating religious values as context-specific resources in organizational behavior. Practically, management is encouraged to foster positive emotions through programs grounded in Islamic values such as gratitude, sincerity, and togetherness, thereby supporting employee well-being and organizational sustainability. Keyword: Positive Emotions, Turnover Intention, Employee Performance, Islamic Banking.